Self-repairing pavement drainage paving structure and construction method thereof

By designing drainage layers and self-repair layers in self-healing asphalt pavement, using graded aggregates, calcium stearate, nanographite sheets and steel wool, the problem of reduced drainage performance after road damage is solved, and better self-healing is achieved Repair and drainage performance.

CN119465727APending Publication Date: 2025-02-18JIANGSU XIANDA CONSTR GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850977.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

After the existing self-repair asphalt pavement is damaged, the stiffness and strength can be partially restored, but the blockage of pores leads to a decrease in drainage performance and is difficult to recover quickly, affecting normal use.

Method used

Using a self-healing pavement drainage pavement structure, including a drainage layer, a self-healing layer and a waterproof bonding layer, the void ratio is adjusted by using graded aggregates, calcium stearate, nanographite sheets and steel wool in the drainage layer. and strength, improve drainage performance and self-healing capabilities.

Benefits of technology

It effectively reduces the pore blockage of asphalt pavement after being subjected to external forces, improves self-repair performance and drainage performance, and enables asphalt pavement to resume normal use faster.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190575690000081
    Figure BDA0005190575690000081
Patent Text Reader

Abstract

The invention relates to the technical field of road engineering, and particularly discloses a self-repairing pavement drainage paving structure and a construction method thereof. A self-repairing pavement drainage paving structure comprises a drainage layer, a self-repairing layer and a waterproof bonding layer, and the self-repairing layer is located between the drainage layer and the waterproof bonding layer; the drainage layer comprises the following raw materials in parts by weight: 50-60 parts of graded aggregate, 30-40 parts of asphalt, 10-20 parts of composite fibers, 5-8 parts of calcium stearate, 3-5 parts of nano graphite flakes and 1-3 parts of steel wool, and the void ratio of the drainage layer is 18-25%; under the synergistic effect of all the components, a paved asphalt pavement is promoted to have relatively good drainage performance and self-repairing capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of road engineering, and more specifically, to a self-repairing road surface drainage paving structure and a construction method thereof. Background Art

[0002] Asphalt roads have the advantages of low noise, good wear resistance and short paving cycle. They have become the main application type in road construction around the world. The complex use environment requires asphalt pavement to have excellent durability, good high and low temperature performance, super self-repairing, etc. This is also the current direction of road material development.

[0003] Existing self-repairing asphalt mainly adds self-repairing microcapsules to asphalt mixtures. When microcracks occur on the road surface, the capsule wall of the microcapsule ruptures and the material in the capsule core is released, thereby delaying the damage to the road surface. However, the repair performance of the microcapsule is limited. After the asphalt road surface is damaged to a certain extent, the stiffness and strength can be partially restored, but the internal pores of the asphalt material are easily blocked, resulting in reduced drainage performance of the road surface. It is also difficult to recover quickly after damage, affecting the normal use of the asphalt road surface. Summary of the invention

[0004] In order to improve the self-repairing and drainage performance of asphalt pavement, the present application provides a self-repairing pavement drainage paving structure and a construction method thereof.

[0005] In the first aspect, the present application provides a self-repairing road drainage paving structure, which adopts the following technical solution: A self-repairing road drainage paving structure comprises a drainage layer, a self-repairing layer and a waterproof bonding layer, wherein the self-repairing layer is located between the drainage layer and the waterproof bonding layer; the drainage layer comprises the following raw materials in parts by weight: 50-60 parts of graded aggregate, 30-40 parts of asphalt, 10-20 parts of composite fiber, 5-8 parts of calcium stearate, 3-5 parts of nanographite sheets, and 1-3 parts of steel wool; the porosity of the drainage layer is 18-25%.

[0006] By adopting the above technical solution, the porosity of the pavement structure is adjusted within an appropriate range, which can maintain good drainage performance of the asphalt pavement, reduce the clogging of pores in the asphalt pavement after being subjected to external forces, and improve the self-repairing performance of the asphalt pavement.

[0007] Calcium stearate is in the form of fine powder and can be filled between asphalt mixture and aggregate to form uniform permeable capillaries, reducing the clogging of pores by excessive asphalt filling into the pores, thereby improving the drainage performance and water loss resistance of the pavement. Nanographite flakes can react chemically with the colloid in asphalt to form a high-strength nano-network structure, enhance the self-adhesion and self-repairing ability of asphalt, and can effectively close the micro-cracks in the asphalt pavement, delaying the expansion and damage of cracks. Nanographite flakes have good thermal conductivity and electrical conductivity, which can help accelerate the drainage of rainwater and the drying of the pavement. At the same time, nanographite flakes can improve the stability and water resistance of asphalt mixtures, reduce water penetration and damage, and improve the drainage performance of asphalt pavements. Steel wool has good flexibility, thermal conductivity and tensile properties, and can transfer heat from the pavement to the roadbed, reduce the occurrence of heat islands, and thus improve the self-repairing effect of asphalt pavements. At the same time, the flexibility and porosity of steel wool can improve the water permeability of asphalt, promote the excretion and evaporation of water, reduce water accumulation and slippery phenomena on asphalt pavement, and improve the drainage performance of asphalt.

[0008] Preferably, the grading of the graded aggregate is as follows: crushed stone with a particle size of 10-15 mm accounts for 40-50% of the total aggregate pass rate, crushed stone with a particle size of 15-10 mm accounts for 30-40% of the total aggregate pass rate, crushed stone with a particle size of 3-5 mm accounts for 5-10% of the total aggregate pass rate, and crushed stone with a particle size ≤3 mm accounts for 8-15% of the total aggregate pass rate.

[0009] By adopting the above technical solution and selecting suitable graded aggregates, a skeleton pore structure can be formed after being mixed with asphalt, thereby maintaining good strength of the asphalt pavement, reducing deformation caused by external forces, and improving the drainage performance and self-repairing ability of the asphalt pavement.

[0010] Preferably, the composite fiber is a mixture of lignin fiber and glass fiber.

[0011] Preferably, the self-repairing layer comprises the following raw materials in parts by weight: 94-96 parts of mineral material, 0.4-0.6 parts of self-repairing asphalt modifier, and 5-10 parts of styrene-butadiene-styrene block copolymer modified asphalt.

[0012] By adopting the above technical solution and using styrene-butadiene-styrene block copolymer modified asphalt instead of base asphalt, the elasticity and toughness of the asphalt pavement can be improved, so that the asphalt pavement has the ability to self-heal when cracks are generated under pressure, can resist the expansion and damage of the cracks, and accelerate the self-repair process of the asphalt pavement.

[0013] Preferably, the self-repairing asphalt modifier comprises the following raw materials in parts by weight: 5-10 parts of sodium silicate, 15-25 parts of nano-silicon dioxide, 5-8 parts of polyphosphoric acid, 10-15 parts of natural latex, and 0.5-0.8 parts of stabilizer.

[0014] By adopting the above technical solution, nano-silicon dioxide and sodium silicate can react with asphalt to generate water-insoluble substances, fill and block the fine cracks in the self-repairing layer, improve the self-healing power and structural strength of the self-repairing layer, and enhance the bonding force between asphalt mixtures when cracked by external forces, reduce the expansion of cracks, and improve the self-repairing ability of the road surface. Polyphosphoric acid can form a colloidal substance at cracks and pores through adsorption and water absorption, which can quickly fill the pores when subjected to external forces to achieve self-repair of the road surface. Polyphosphoric acid can react chemically with asphalt molecules in asphalt mixtures to form strong chemical bonds, enhance the bonding force between asphalt, and thus improve the strength and crack resistance of the road surface. At the same time, polyphosphoric acid is compounded with natural latex to improve the elastic recovery ability and high temperature resistance of asphalt mixtures, enable asphalt pavements to withstand greater driving pressure and driving loads, and improve the fatigue life and self-repairing performance of asphalt.

[0015] Preferably, the stabilizer is a mixture of a wax-based stabilizer and a silane-based stabilizer, and the mass ratio of the wax-based stabilizer to the silane-based stabilizer is 1:(0.5-0.8).

[0016] By adopting the above technical solution, silane-based stabilizers and wax-based stabilizers can improve the adhesion of natural latex in asphalt mixtures, promote self-healing ability of self-repairing mixtures, and improve the self-repairing performance of asphalt pavement. At the same time, wax-based stability can better improve the anti-aging performance of asphalt, increase the rutting factor of asphalt mixtures, and improve the fatigue life and self-repairing ability of asphalt pavement.

[0017] Preferably, the waterproof bonding layer is styrene-butadiene-styrene block copolymer modified asphalt.

[0018] In a second aspect, the present application provides a construction method for a self-repairing road drainage pavement structure, which adopts the following technical solution: A construction method of a self-repairing road drainage paving structure comprises the following specific steps: A waterproof bonding layer and a self-repairing layer are laid on the road surface in sequence, and then the graded aggregate, asphalt, calcium stearate, nano-graphite flakes and steel wool are mixed evenly at 110-140°C to form a drainage layer mixture, and then the drainage layer mixture is laid on the surface of the self-repairing layer to form a drainage layer, and the drainage layer is rolled at 90-110°C to obtain a self-repairing road drainage pavement structure.

[0019] By adopting the above technical solution and combining the various components, the asphalt pavement can have a better drainage effect while maintaining good self-repair performance and strength.

[0020] Preferably, the thickness of the self-repairing layer is 1.5-2.5 cm, the thickness of the waterproof adhesive layer is 1.5-2 mm, and the thickness of the drainage layer is 3-7 cm.

[0021] Preferably, sodium silicate, nano-silicon dioxide, polyphosphoric acid, a stabilizer and natural latex are mixed to form a self-repairing asphalt modifier, and then the self-repairing asphalt modifier, mineral material and styrene-butadiene-styrene block copolymer modified asphalt are mixed to form a self-repairing mixture; Spraying styrene-butadiene-styrene block copolymer modified emulsified asphalt on the road surface to obtain a waterproof bonding layer, then spreading a self-repairing layer mixture on the waterproof bonding layer, and rolling the self-repairing layer mixture at 90-110° C. to form a self-repairing layer; Then, the graded aggregate, asphalt, calcium stearate, nano-graphite flakes and steel wool are evenly mixed at 110-140°C to form a drainage layer mixture, and then the drainage layer mixture is paved on the surface of the self-repairing layer, and the drainage layer mixture is rolled at 90-110°C to form a drainage layer, thereby obtaining a self-repairing pavement drainage paving structure.

[0022] In summary, this application has the following beneficial effects: 1. Since the application uses graded aggregate, calcium stearate, nanographite flakes, and steel wool to adjust the asphalt mixture to have a more appropriate porosity and strength, the pore blockage of the asphalt pavement after being subjected to external force is reduced, and the self-repairing performance of the asphalt pavement is improved. At the same time, calcium stearate is used to form uniform water-permeable capillaries between the asphalt mixture and the aggregate, and the nanographite flakes and the colloid in the asphalt form a high-strength nano-network structure, which helps to accelerate the drainage of rainwater and the drying of the road surface, and enhance the self-adhesion and self-repairing ability of asphalt.

[0023] 2. In this application, sodium silicate and nano-silicon dioxide are used in the self-repairing asphalt modifier to fill and block the fine cracks in the self-repairing layer, enhance the bonding force between the asphalt mixture, and improve the self-healing power and structural strength of the self-repairing layer. The use of polyphosphoric acid and natural latex compound can form a colloid in the cracks and pores of the asphalt mixture, quickly fill the pores when subjected to external force, and realize the self-repair of the road surface. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] The styrene-butadiene-styrene block copolymer modified asphalt selects the ID grade produced by Foshan Gaofu PetroChina Fuel Asphalt Co., Ltd.

[0026] Example of preparation of drainage layer mix Preparation Example 1 The drainage layer mixture includes the following raw materials in parts by weight: 55kg of graded aggregate, 35kg of asphalt, 15kg of composite fiber, 7kg of calcium stearate, 4kg of nano-graphite flakes, and 2kg of steel wool, wherein the grading of the aggregate is as follows: crushed stone with a particle size of 10-15mm accounts for 50% of the total aggregate pass rate, crushed stone with a particle size of 15-10mm accounts for 35% of the total aggregate pass rate, crushed stone with a particle size of 3-5mm accounts for 8% of the total aggregate pass rate, and crushed stone with a particle size ≤3mm accounts for 12% of the total aggregate pass rate. The composite fiber is a mixture of lignin fiber and glass fiber, and the mass ratio of lignin fiber to glass fiber is 1:1. The average diameter of the steel wool is 0.5mm, the size of the nano-graphite flakes is 0.5-10μm, and the thickness is 10-20nm. The asphalt is Maoming Petrochemical No. 70 Grade A asphalt.

[0027] The method for preparing the drainage layer mixture comprises the following specific steps: The graded aggregate, asphalt, calcium stearate, nano-graphite flakes and steel wool are mixed at 120° C. and stirred evenly to form a drainage layer mixture.

[0028] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of graded aggregate used in the drainage layer mixture raw materials is 50 kg, the amount of asphalt used is 40 kg, the amount of composite fiber used is 20 kg, the amount of calcium stearate used is 5 kg, the amount of nano-graphite flakes used is 3 kg, and the amount of steel wool used is 1 kg.

[0029] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of graded aggregate used in the drainage layer mixture raw materials is 60 kg, the amount of asphalt used is 30 kg, the amount of composite fiber used is 10 kg, the amount of calcium stearate used is 8 kg, the amount of nano-graphite flakes used is 5 kg, and the amount of steel wool used is 3 kg.

[0030] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that calcium stearate is not used in the raw materials of the drainage layer mixture.

[0031] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that no nanographite flakes and steel wool are used in the raw materials of the drainage layer mixture.

[0032] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that an equal amount of mineral powder is used in the raw materials of the drainage layer mixture instead of the graded aggregate, and the average particle size of the mineral powder is 5-15 mm.

[0033] Preparation example of self-healing layer mixture Preparation Example 7 The self-repairing layer mixture includes the following raw materials in parts by weight: 95 kg of mineral material, 0.5 kg of self-repairing asphalt modifier, and 8 kg of styrene-butadiene-styrene block copolymer modified asphalt, wherein the self-repairing asphalt modifier is sodium silicate, the mineral material is mineral powder, and the average particle size of the mineral powder is 1-5 mm.

[0034] The method for preparing the self-repairing layer mixture comprises the following specific steps: The mineral material, the self-repairing asphalt modifier and the styrene-butadiene-styrene block copolymer modified asphalt are mixed, and stirred evenly at 100° C. to form a self-repairing layer mixture.

[0035] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 7 is that the amount of mineral material used in the self-repairing layer mixture raw material is 94 kg, the amount of self-repairing asphalt modifier used is 0.6 kg, and the amount of styrene-butadiene-styrene block copolymer modified asphalt used is 5 kg.

[0036] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 7 is that the amount of mineral material used in the self-repairing layer mixture raw material is 96 kg, the amount of self-repairing asphalt modifier used is 0.4 kg, and the amount of styrene-butadiene-styrene block copolymer modified asphalt used is 10 kg.

[0037] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that the raw material of the self-repairing asphalt modifier in the self-repairing layer mixture includes the following components in parts by weight: 8 kg of sodium silicate, 20 kg of nano-silicon dioxide, 7 kg of polyphosphoric acid, 13 kg of natural latex, and 0.8 kg of stabilizer. The stabilizer is a silane-based stabilizer, which is polymethylsiloxane, and the molecular weight of polymethylsiloxane is 3000.

[0038] The method for preparing the self-repairing layer mixture comprises the following specific steps: Sodium silicate, nano-silica, polyphosphoric acid and natural latex are mixed in advance, and then a stabilizer is added and stirred evenly to form a self-repairing asphalt modifier; mineral materials, self-repairing asphalt modifier and styrene-butadiene-styrene block copolymer modified asphalt are mixed, and stirred evenly at 100°C to form a self-repairing layer mixture.

[0039] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 10 is that the amount of sodium silicate used in the self-repairing asphalt modifier raw material is 5 kg, the amount of nano-silicon dioxide used is 25 kg, the amount of polyphosphoric acid used is 5 kg, the amount of natural latex used is 10 kg, and the amount of stabilizer used is 0.5 kg.

[0040] Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 10 is that the amount of sodium silicate used in the self-repairing asphalt modifier raw material is 10 kg, the amount of nano-silicon dioxide used is 15 kg, the amount of polyphosphoric acid used is 8 kg, the amount of natural latex used is 15 kg, and the amount of stabilizer used is 0.8 kg.

[0041] Preparation Example 13 The difference between Preparation Example 13 and Preparation Example 10 is that the stabilizer in the raw material of the self-repairing asphalt modifier is a mixture of a wax-based stabilizer and a silane-based stabilizer, and the mass ratio of the wax-based stabilizer to the silane-based stabilizer is 1:0.7, wherein the wax-based stabilizer is polyethylene wax, and the molecular weight of the polyethylene wax is 1000.

[0042] Preparation Example 14 The difference between Preparation Example 14 and Preparation Example 10 is that natural latex and polyphosphoric acid are not used in the raw materials of the self-repairing asphalt modifier. Example

[0043] Example 1 The present embodiment provides a self-repairing road drainage paving structure, including a drainage layer, a self-repairing layer, and a waterproof bonding layer, which are, from bottom to top, a waterproof bonding layer, a self-repairing layer, and a drainage layer, wherein the drainage layer is derived from the drainage layer mixture prepared in Preparation Example 1, the self-repairing layer is derived from the self-repairing layer mixture prepared in Preparation Example 7, and the waterproof bonding layer is styrene-butadiene-styrene block copolymer modified asphalt.

[0044] The construction method of the self-repairing road drainage paving structure includes the following specific steps: Spray styrene-butadiene-styrene block copolymer modified asphalt on the road surface in advance to obtain a waterproof bonding layer with an average thickness of 1.5-2mm, then spread the self-repairing layer mixture on the waterproof bonding layer, and roll the self-repairing layer mixture at 100°C to form a self-repairing layer with an average thickness of 2cm. Finally, spread the drainage layer mixture on the surface of the self-repairing layer, and roll the drainage layer mixture at 100°C to form a drainage layer with an average thickness of 5cm and a porosity of 22%, thereby completing the construction of the self-repairing pavement drainage pavement structure.

[0045] Example 2 The difference between Example 2 and Example 1 is that the drainage layer in the self-repairing pavement drainage pavement structure comes from the drainage layer mixture prepared in Preparation Example 2, and the self-repairing layer comes from the self-repairing layer mixture prepared in Preparation Example 8.

[0046] Example 3 The difference between Example 3 and Example 1 is that the drainage layer in the self-repairing pavement drainage pavement structure comes from the drainage layer mixture prepared in Preparation Example 3, and the self-repairing layer comes from the self-repairing layer mixture prepared in Preparation Example 9.

[0047] Example 4 The difference between Example 4 and Example 1 is that the self-repairing layer in the self-repairing pavement drainage pavement structure is derived from the self-repairing layer mixture prepared in Preparation Example 10.

[0048] Example 5 The difference between Example 5 and Example 1 is that the self-repairing layer in the self-repairing pavement drainage pavement structure is derived from the self-repairing layer mixture prepared in Preparation Example 11.

[0049] Example 6 The difference between Example 6 and Example 1 is that the self-repairing layer in the self-repairing pavement drainage pavement structure comes from the self-repairing layer mixture prepared in Preparation Example 12.

[0050] Example 7 The difference between Example 7 and Example 1 is that the self-repairing layer in the self-repairing pavement drainage pavement structure is derived from the self-repairing layer mixture prepared in Preparation Example 13.

[0051] Example 8 The difference between Example 8 and Example 1 is that the self-repairing layer in the self-repairing pavement drainage pavement structure is derived from the self-repairing layer mixture prepared in Preparation Example 14.

[0052] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the drainage layer in the self-repairing pavement drainage pavement structure is derived from the drainage layer mixture prepared in Preparation Example 4.

[0053] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the drainage layer in the self-repairing pavement drainage pavement structure is derived from the drainage layer mixture prepared in Preparation Example 5.

[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the drainage layer in the self-repairing pavement drainage pavement structure is derived from the drainage layer mixture prepared in Preparation Example 6.

[0055] Performance testing The following performance tests were conducted on the self-repairing pavement drainage pavement structures provided in Examples 1-8 and Comparative Examples 1-3 of the present application. The specific test results are shown in Table 1.

[0056] Detection Methods 1. Drainage performance A new type of pavement water permeability meter was used to evaluate the water permeability of the pavement, and its drainage performance was tested according to T0730 in the Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering (JTG E20-2011).

[0057] 2. Crack resistance and self-repair performance The self-repairing pavement drainage pavement structure prepared in this application was tested by a -10°C three-point beam bending test, and the specimens that had undergone the three-point beam bending test were realigned and wrapped with tape, and then placed in a microwave oven for microwave-accelerated assisted self-repair, and the -10°C three-point beam bending test was performed again on the self-repaired specimens.

[0058] Table 1: Performance test results data table From the performance test results, it can be seen that under the synergistic effect of each component in the embodiment, the self-repairing road drainage pavement structure prepared in this application has good self-repairing ability and also maintains good drainage effect. In Examples 1-3, the usage amount of each component is different, among which Example 1 has better comprehensive performance.

[0059] In Examples 4-6, self-repairing asphalt modifiers of different components were added to the self-repairing layer mixture. From the performance test results, it can be seen that the crack resistance of the asphalt pavement is significantly improved. At the same time, the self-healing ability of the asphalt pavement is also improved, reducing the expansion of cracks.

[0060] By comparing Examples 7-8 with Example 4, it can be seen that in Example 7, a mixture of a wax-based stabilizer and a silane-based stabilizer is used as a stabilizer for the self-repairing asphalt modifier. From the performance test results, it can be seen that the comprehensive performance of the asphalt pavement is improved. In Example 8, natural latex and polyphosphoric acid are not used. From the performance test results, it can be seen that the self-repairing ability and drainage performance of the asphalt pavement are significantly reduced. It is further explained that the compounding of polyphosphoric acid and natural latex can significantly improve the elastic recovery ability and self-repairing ability of the asphalt mixture and improve the fatigue life of the asphalt.

[0061] By comparing Comparative Examples 1-3 with Example 1, it can be seen that Comparative Example 1 does not use calcium stearate, Comparative Example 2 does not use nanographite sheets and steel wool, and Comparative Example 3 uses an equal amount of mineral powder instead of graded aggregate. From the performance test results, it can be seen that the drainage performance and self-repairing ability of the asphalt pavement are significantly reduced. It is further explained that the present application maintains a good porosity of the asphalt pavement through the synergistic effect of each component, forms a high-strength cross-linked nano-network structure, enhances the self-adhesion and self-repairing ability of asphalt, can effectively close the micro cracks of the asphalt pavement, and improves the drainage performance and self-repairing ability of the asphalt pavement.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A self-repairing road drainage paving structure, characterized in that: It includes a drainage layer, a self-repairing layer and a waterproof bonding layer, wherein the self-repairing layer is located between the drainage layer and the waterproof bonding layer; the drainage layer includes the following raw materials in parts by weight: 50-60 parts of graded aggregate, 30-40 parts of asphalt, 10-20 parts of composite fiber, 5-8 parts of calcium stearate, 3-5 parts of nanographite sheets, and 1-3 parts of steel wool, and the porosity of the drainage layer is 18-25%.

2. The self-repairing road drainage paving structure according to claim 1, characterized in that: The grading method of the graded aggregate is as follows: crushed stone with a particle size of 10-15mm accounts for 40-50% of the total aggregate passing rate, crushed stone with a particle size of 15-10mm accounts for 30-40% of the total aggregate passing rate, crushed stone with a particle size of 3-5mm accounts for 5-10% of the total aggregate passing rate, and crushed stone with a particle size ≤3mm accounts for 8-15% of the total aggregate passing rate.

3. The self-repairing road drainage paving structure according to claim 1, characterized in that: The composite fiber is a mixture of lignin fiber and glass fiber.

4. The self-repairing road drainage paving structure according to claim 1, characterized in that: The self-repairing layer comprises the following raw materials in parts by weight: 94-96 parts of mineral material, 0.4-0.6 parts of self-repairing asphalt modifier, and 5-10 parts of styrene-butadiene-styrene block copolymer modified asphalt.

5. The self-repairing road drainage paving structure according to claim 4, characterized in that: The self-repairing asphalt modifier comprises the following raw materials in parts by weight: 5-10 parts of sodium silicate, 15-25 parts of nano silicon dioxide, 5-8 parts of polyphosphoric acid, 10-15 parts of natural latex, and 0.5-0.8 parts of stabilizer.

6. The self-repairing road drainage paving structure according to claim 5, characterized in that: The stabilizer is a mixture of a wax-based stabilizer and a silane-based stabilizer, and the mass ratio of the wax-based stabilizer to the silane-based stabilizer is 1:(0.5-0.8).

7. The self-repairing road drainage paving structure according to claim 1, characterized in that: The waterproof bonding layer is styrene-butadiene-styrene block copolymer modified asphalt.

8. A construction method of a self-repairing road drainage pavement structure according to any one of claims 1 to 7, characterized in that: The specific steps include: A waterproof bonding layer and a self-repairing layer are laid on the road surface in sequence, and then the graded aggregate, asphalt, calcium stearate, nano-graphite flakes and steel wool are mixed evenly at 110-140°C to form a drainage layer mixture, and then the drainage layer mixture is laid on the surface of the self-repairing layer to form a drainage layer, and the drainage layer is rolled at 90-110°C to obtain a self-repairing road drainage pavement structure.

9. The construction method of the self-repairing road drainage pavement structure according to claim 8, characterized in that: The thickness of the self-repairing layer is 1.5-2.5 cm, the thickness of the waterproof bonding layer is 1.5-2 mm, and the thickness of the drainage layer is 3-7 cm.

10. The construction method of the self-repairing road drainage pavement structure according to claim 8, characterized in that: Sodium silicate, nano-silicon dioxide, polyphosphoric acid, a stabilizer and natural latex are mixed to form a self-repairing asphalt modifier, and then the self-repairing asphalt modifier, mineral material and styrene-butadiene-styrene block copolymer modified asphalt are mixed to form a self-repairing mixture; Spraying styrene-butadiene-styrene block copolymer modified emulsified asphalt on the road surface to obtain a waterproof bonding layer, then spreading a self-repairing layer mixture on the waterproof bonding layer, and rolling the self-repairing layer mixture at 90-110° C. to form a self-repairing layer; Then, the graded aggregate, asphalt, calcium stearate, nano-graphite flakes and steel wool are evenly mixed at 110-140°C to form a drainage layer mixture, and then the drainage layer mixture is paved on the surface of the self-repairing layer, and the drainage layer mixture is rolled at 90-110°C to form a drainage layer, thereby obtaining a self-repairing pavement drainage paving structure.